Efficient quantum circuit design - Lim, Eugene Zhi Jie (Nanyang Technological University, 2024)
In this project, we focus on designing modular quantum division circuits with quantum addition circuits as its interchangeable component. A Design Space Exploration approach is then used to find the addition circuit that creates the optimal implementation of our division circuit in terms of logical depth and size.